2005
DOI: 10.1104/pp.104.056077
|View full text |Cite
|
Sign up to set email alerts
|

Reductions of Rubisco Activase by Antisense RNA in the C4 Plant Flaveria bidentis Reduces Rubisco Carbamylation and Leaf Photosynthesis

Abstract: To function, the catalytic sites of Rubisco (EC 4.1.1.39) need to be activated by the reversible carbamylation of a lysine residue within the sites followed by rapid binding of magnesium. The activation of Rubisco in vivo requires the presence of the regulatory protein Rubisco activase. This enzyme is thought to aid the release of sugar phosphate inhibitors from Rubisco's catalytic sites, thereby influencing carbamylation. In C 3 species, Rubisco operates in a low CO 2 environment, which is suboptimal for both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 58 publications
1
26
0
Order By: Relevance
“…In rice, about 30% reduction in the Rubisco activase content led to 50% decrease in steadystate photosynthesis at high light in ambient air conditions (Jin et al, 2006), while the photosynthetic rates were unchanged until Rubisco activase contents decreased to 10% of that in control plants in tobacco (Mate et al, 1993) and Arabidopsis (Eckardt et al, 1997) and 30% of that in Flaveria bidentis (von Caemmerer et al, 2005). These results suggested that Rubisco activase in rice leaves has greater effects on photosynthesis compared with other plant species.…”
mentioning
confidence: 48%
See 1 more Smart Citation
“…In rice, about 30% reduction in the Rubisco activase content led to 50% decrease in steadystate photosynthesis at high light in ambient air conditions (Jin et al, 2006), while the photosynthetic rates were unchanged until Rubisco activase contents decreased to 10% of that in control plants in tobacco (Mate et al, 1993) and Arabidopsis (Eckardt et al, 1997) and 30% of that in Flaveria bidentis (von Caemmerer et al, 2005). These results suggested that Rubisco activase in rice leaves has greater effects on photosynthesis compared with other plant species.…”
mentioning
confidence: 48%
“…In order to clarify the effect of Rubisco activase on photosynthesis, transgenic plants with reduced Rubisco activase contents have been produced by the antisense RNA or RNAi technology in some plant species, tobacco (Mate et al, 1993), Arabidopsis thaliana (Eckardt et al, 1997), rice (Jin et al, 2004(Jin et al, , 2006 and Flaveria bidentis (von Caemmerer et al, 2005). In rice, about 30% reduction in the Rubisco activase content led to 50% decrease in steadystate photosynthesis at high light in ambient air conditions (Jin et al, 2006), while the photosynthetic rates were unchanged until Rubisco activase contents decreased to 10% of that in control plants in tobacco (Mate et al, 1993) and Arabidopsis (Eckardt et al, 1997) and 30% of that in Flaveria bidentis (von Caemmerer et al, 2005).…”
mentioning
confidence: 99%
“…By transforming the C 4 plant Flaveria bidentis with an antisense RCA gene, von Caemmerer et al (2005) showed that RCA activity was essential for the proper functioning of the C 4 photosynthetic pathway. In maize, which is also a C 4 plant, the RCA protein content of leaves during grain filling was higher in high-yield populations than in low-yield populations (Martı'nez-Barajas et al, 1997; Morales et al, 1999).…”
Section: The Expression Levels Of Zmrcaa and Zmrcab Could Modulate Grmentioning
confidence: 99%
“…The activities of RCA are thought to be key regulation points for photosynthesis under different environmental stress conditions (Crafts-Brandner and Salvucci, 2000;Pollock et al, 2003). Plants expressing reduced levels of RCA exhibit decreased levels of P N and/or growth (Mate et al, 1996;Eckardt et al, 1997;He et al, 1997), and those with very low or no RCA expression cannot survive in atmospheric CO 2 (Somerville et al, 1982;Salvucci et al, 1985Salvucci et al, , 1986Mate et al, 1993;von Caemmerer et al, 2005). These results make modulation of RCA an attractive experimental goal for the improvement of CO 2 fixation rates and, ultimately, crop productivity.…”
mentioning
confidence: 99%